Study on the soil arching effect and evolution mechanism of anti-sliding pile in accumulation layers landslides under reservoir water level fluctuations - Li, Guangbo; Zhou, Chunmei; Qin, Zihan; Xing, Haiguang (Frontiers in Earth Science, 2025)
This study focuses on the Shilongmen landslide in the Three Gorges Reservoir area, investigating the evolution of the soil arching effect and its influencing factors in the context of landslide disaster prevention and control. Through field investigation, theoretical analysis, and FLAC3D numerical simulations, the effects of factors such as reduced soil strength parameters, and soil slip in front of piles on the soil arching effect were systematically analyzed. The numerical simulations specifically examined the stress distribution of the soil arching effect along the depth direction and its stages of evolution during the landslide process. The results indicate that when soil strength parameters are low, stress variations along the soil depth increase. As strength parameters continue to decrease, the load-bearing capacity of the soil arching effect weakens, resulting in increased internal stress within the landslide body. Soil slip in front of the piles significantly reduces the frictional soil arching effect, with stress in the surface soil decreasing by approximately 50%. The study identified three stages of the soil arching effect: initiation, development, and failure. Under the combined influence of multiple factors, the friction soil arch slides along the sides of the anti-slide piles, while the bearing capacity of the soil at the end-bearing soil arch is approximately 1.5 times higher than that of the friction soil arch. Due to deformation incompatibility between anti-slide piles and the surrounding soil, pile-soil separation may occur, suggesting that anti-slide pile designs should incorporate baffle structures to enhance overall stability. These findings provide a novel perspective and approach for optimizing anti-slide pile design and landslide disaster prevention, contributing to improved safety and reliability in landslide mitigation engineering.